2015
DOI: 10.1155/2015/794718
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of the Carmine Spider Mite,Tetranychus cinnabarinus(Boisduval, 1867) (Acari: Tetranychidae), and Its Response toβ-Sitosterol

Abstract: Tetranychus cinnabarinus (Acari: Tetranychidae) is a worldwide polyphagous agricultural pest that has the title of resistance champion among arthropods. We reported previously the identification of the acaricidal compound β-sitosterol from Mentha piperita and Inula japonica. However, the acaricidal mechanism of β-sitosterol is unclear. Due to the limited genetic research carried out, we de novo assembled the transcriptome of T. cinnabarinus using Illumina sequencing and conducted a differential expression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
0
14
1
Order By: Relevance
“…Additionally, 41,716 (68.96%) were not annotated and may represent genes without detectable homologies. The number of annotated unigenes is lower than the results reported by other research groups for other invertebrate species [23,24], indicating that our knowledge of P. pseudoannulata genes is limited. Further research is needed to characterize these genes and explore their functions.…”
Section: Resultscontrasting
confidence: 66%
See 1 more Smart Citation
“…Additionally, 41,716 (68.96%) were not annotated and may represent genes without detectable homologies. The number of annotated unigenes is lower than the results reported by other research groups for other invertebrate species [23,24], indicating that our knowledge of P. pseudoannulata genes is limited. Further research is needed to characterize these genes and explore their functions.…”
Section: Resultscontrasting
confidence: 66%
“…Numerous studies focused on metal transporters in both plants and animals have been reported [19,23,39,40]. ATP-binding cassette (ABC) family transporters are important heavy metal transporters and interact with a wide range of chemicals including metals by pumping them across the cell membrane to maintain of cellular metal homeostasis [41,42].…”
Section: Resultsmentioning
confidence: 99%
“…2B). The average length of unigenes in our sequencing and assembly data was higher than Nilaparvata lugens (434 bp) (Xue et al 2010) and Plutella xylostella larval midgut transcriptome (416 bp) (Xie et al 2012) and lower than Tetranychus cinnabarinus transcriptome (1468 bp) (Bu et al 2015) conducted using Illumina NGS.…”
Section: Sequencing Quality Control and Transcriptome Assemblymentioning
confidence: 74%
“…) and lower than Tetranychus cinnabarinus transcriptome (1468 bp) (Bu et al . ) conducted using Illumina NGS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation